Natural Bioactive Compounds of Sechium spp. for Therapeutic and Nutraceutical Supplements - Iñiguez-Luna, María Isabel; Cadena-Iñiguez, Jorge; Soto-Hernández, Ramón Marcos; Morales-Flores, Francisco Javier; Cortes-Cruz, Moisés; Watanabe, Kazuo N. (Frontiers in Plant Science, 2021)
Natural products are in great demand because certain secondary metabolites (SMs) are sources of antioxidants, flavourings, active substances, or anticancer agents with less aggressiveness and selectivity, among which triterpenes and flavonoids are of importance because they inhibit carcinogenesis. For Sechium spp. P. Br. (chayotes), there is scientific evidence of antiproliferative activity that has occurred when cancer cell lines have been treated with this fruit. In order to compare future therapeutic designs and identify new and ancestral characteristics, triterpenes and flavonoids were determined in contrasting Sechium genotypes. The obtained data were analyzed via a cladistics approach, with the aim of identifying the characteristics and state of phytochemicals and genetic variables. The concentrations of flavonoids and triterpenes were determined, and a more complex composition of secondary metabolites was found in the wild types as compared to their domesticated genotypes. Bitter fruits contained a higher number of SMs, followed by those with a neutral and sweet flavour. A cladogram showed the differentiation of the three groups based on the flavour of the fruits. The diversity of SMs decreases in evolutionary terms, in response to domestication and environmental adaptation. Therefore, genotypes can be feasibly selected based on fruit flavour for gross-breeding, and cytotoxicity can be reduced without losing possible therapeutic effects.